IMMUNOPATHOLOGICAL STUDIES OF CANINE RABIES IN FAISALABAD, PAKISTAN - W. Ahmad; F. Mahmood; Y. Li; M. Duan; Z. Guan; M. Zhang; M. A. Ali; Z. Liu (Journal of Animal and Plant Sciences, 2016)
Rabies is a fatal disease particularly in developing countries like Pakistan, where annual death toll ranges from 2,000 to 5,000 due to insufficient prophylactic measures. The present study was conducted to screen out randomly selected stray dogs (n= 80) for rabies virus at eight sites in the district of Faisalabad, Pakistan. Brain samples were surgically removed and fixed in neutral buffer formalin. Paraffin-embedded brain tissues were processed for the diagnosis of the rabies virus using immuno histochemistry and histopathology. Post dog-bite vaccine data from the year 2006 to 2010 were obtained from two public hospitals in district Faisalabad. The highest number of rabies cases was found in 2010 (n=1,980) while, the lowest number of anti-rabies shots (n=312) was injected in 2009. Most importantly, only 3.75% of brain samples were diagnosed positive for rabies virus. Considerable immuno-reactivity and characteristic pathological lesions (neuronal degeneration, babe’s nodules and Negri bodies) were observed in granular and Purkinje cells of the cerebrum and cerebellum respectively. Proper monitoring and regulatory framework are essentially required to fully eradicate rabies cases from rural and urban areas of Pakistan.
Keywords: Brain; rabies virus; dog bite; immune histochemistry; histopathology; stray dog